Stakeholder perspectives on hearing conservation programmes in the South African mining sector: A qualitative study - Nomfundo Moroe; Katijah Khoza-Shangase (Health Research Policy and Systems)
Abstract Purpose Stakeholders play a crucial role in the success of complex interventions, such as hearing conservation programmes (HCPs), where their active participation directly impacts outcomes. This study aimed to investigate the views of various stakeholders, involved in occupational noise management, in the mining sector in South Africa. Methods A cross-sectional qualitative study was conducted, recruiting 16 participants through purposive and snowball sampling techniques. Participants represented diverse roles, including Mine Health and Safety officials, audiologists, ventilation and occupational health engineers and an occupational hygiene assistant. In-depth interviews were conducted to gather data, which were later analysed using inductive thematic analysis to identify emerging themes. Results The in-depth interviews revealed six prominent themes that shed light on both the facilitators and barriers to achieving desired milestones in the implementation of HCPs. These themes were crisis management; some are more equal than others; we have tried, but then reality intervenes; cost of an individual’s hearing; knowledge is power; and show and tell. Conclusion Achieving milestones requires a comprehensive and systematic approach, fostering collaborative engagement among all stakeholders in the mining industry. By viewing and treating HCPs as complex interventions, occupational healthcare can be improved for individuals exposed to excessive noise in the workplace. The study highlights the need for careful consideration of stakeholder perspectives to ensure the feasibility and effectiveness of interventions aimed at eliminating excessive noise in the mining industry.